Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

It is my thinking that unique conventionally means special or one of its kind. But in the context of solving functional equations*, I am confused what it means to have a unique solution...

*e.g. Find solution(s) to $f(x+y)+f(x-y)=2x^2+2y^2$

share|cite|improve this question
A unique solution means it is the only solution. In your example: if $(x_0, y_0)$ solves your equation then it is called unique iff the following statement is true: if $(x_1, y_1)$ solves the equation, then this implies $x_0= x_1, y_0 = y_1$. – user20266 Dec 31 '11 at 17:35
@Thomas: As it is a functional equation, one would be looking for functions $f$ that satisfy that property for all $x$ and $y$, such as $f(t)=t^2$. – Zev Chonoles Dec 31 '11 at 17:40
How do we prove that a solution is "unique" then? Also, am I right in understanding that x=-1 is a unique solution to (x+1)^2=0 then? – MathMathCookie Dec 31 '11 at 17:42
up vote 2 down vote accepted

It means just what you'd think; if $f$ and $g$ are two solutions to the functional equation, then $f=g$, i.e. $f(t)=g(t)$ for all $t$ in the domain.

In the problem you've given, we can prove that there is a unique solution as follows: suppose $f$ is some solution to the functional equation$$f(x+y)+f(x-y)=2x^2+2y^2,$$ i.e. $f(x+y)+f(x-y)=2x^2+2y^2$ for all $x$ and $y$. Then, in particular, we have that $$f(x+0)+f(x-0)=2x^2+2\cdot 0^2$$ $$2f(x)=2x^2$$ and therefore $f(x)=x^2$. Thus the function $f(t)=t^2$ is the only solution to the functional equation $f(x+y)+f(x-y)=2x^2+2y^2$.

Here's a functional equation that does not have a unique solution: $f(x)^2=x^2$. For example, all of the functions $$f(t)=t,\qquad g(t)=-t,\qquad h(t)=|t|$$ satisfy the function equation, i.e. $f(x)^2=x^2$ for all $x$, $g(x)^2=(-x)^2=x^2$ for all $x$, and $h(x)^2=|x|^2=x^2$ for all $x$. However, $f$, $g$, and $h$ are different functions: for example, $$f(1)=1\neq-1=g(1)$$ so $f\neq g$, and similarly $f\neq h$ and $g\neq h$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.